Communication in the state of crisis - Senić Vladimir; Senić Radoslav (Marketing (Beograd. 1991), 2015)
Due to diversity of research related to crisis it is rather important to present definitions of various key terms related to crisis, crisis management and crisis communication, in order to establish tangible boundaries among them. Those three are mutually intertwined and should be considered starting from the first symptoms of crisis to crisis management and finally crisis communication. In the state of crisis, conventional management practice is often not adequate, while types of reaction are insufficient. Thus, this paper gives precise definitions of crisis, crisis management and crisis communication.